Coronary angiographic profile in patients with failed thrombolysis - M, Saravanan; Balakrishnan, Vinodkumar; TR, Muralidharan (Journal of Cardiovascular Medicine and Cardiology, 2019)
Background: Acute Myocardial Infarction (MI) is a life threatening condition responsible for over 85% of the deaths all over the world. The management of MI has to be done on an emergency footing, without losing any time. The standard protocol involves thrombolysis in these patients. However, not all the thrombolysis procedures turn out to be successful. This study was done to explore the prevalence and risk factors associated with the success of thrombolysis. Methods: This cross sectional study was carried out among 59 patients who were admitted to our tertiary care hospital with a diagnosis of acute ST segment elevation MI and started on thrombolysis. Patients who were contraindicated for thrombolysis were excluded from the study. A 12 lead electrocardiography was done prior and 60 minutes after initiation of thrombolysis. Echocardiogram was done to evaluate the left ventricle function. Coronary angiogram was carried out to assess the vascular abnormalities. Results: Out the total 59 patients in the study group, 31 patients belonged to successful thrombolysis group and 28 patients belonged to the failed thrombolysis group. It was observed that patients with diabetes mellitus had a significant rise in the number of failed thrombolysis compared to those without diabetes mellitus (p<0.005). It was observed that anterior wall MI was significantly at risk for a failure in thrombolysis (82.1%) compared to inferior wall MI (17.8%). Conclusions: Failed thrombolysis was more common in patients who had diabetes as risk factor. Moreover anterior wall MI proved to be increasingly at risk for failure of thrombolysis. This study proves that screening of risk factors prior to the initiation of thrombolysis will help in devising alternative treatment procedures so that the failure rates can be minimized and resources may be redirected to effective treatment modalities.